Community perception of coral reefs in Golfo Dulce: bases for social integration in restoration programs. - Villalobos Cubero, Tatiana (2023)
Introduction: Addressing the accelerated coral reefs degradation requires integrated action at multiple social and ecological scales. At local level, active participation of the main users must be included. Objective: To evaluate local knowledge and perception about coral reefs in Golfo Dulce to generate bases for social integration in coral restoration. Methods: 183 interviews were conducted in coastal communities in Golfo Dulce, between September 2016 and March 2017. The interviewees were classified as: (1) Artisanal fishing (PA) = 57 interviewees, (2) Tourism (T) = 62, and (3) Others (O) = 64. The first part of the interview was about knowledge and a grade was assigned based on correct answers. According to the grade, they were classified as informed, medium information or uninformed. The second part was based on perception scales on: (I) visitation, (II) factors that damage coral reefs, (III) management measures, and (IV) health of marine resources in Golfo Dulce. Results: Group T had the highest percentage of informed interviewees = 42 % and group O uninformed = 37 %. The second part was perception, more than 50 % of PA and T consider that the visit is frequent. Sedimentation and contamination by agrochemicals were identified by more than 60 % of PA and T as the main threat. 35 % of PA and 40 % of T perceive permanent buoys as the best measure for the Golfo Dulce. The visitation restriction was the measure with the least acceptance. 60 % of the interviewees of PA and T consider that the marine resources of the gulf will be worse than today. Conclusions: These results confirm the importance of understading coral reefs users knowledge and perception in participatory and educational processes in coral reef restoration and conservation.